CLA+ T Cell Response to Microbes in Psoriasis - De Jesús-Gil, Carmen; Ruiz-Romeu, Ester; Ferran, Marta; Chiriac, Anca; Deza, Gustavo; Hóllo, Péter; Celada, Antonio; Pujol, Ramon M.; Santamaria-Babí, Luis F. (Frontiers in Immunology, 2018)
Streptococcus pyogenes throat infection is a clinically relevant trigger of both guttate and chronic plaque psoriasis, and it provides an ideal context in which to study the pathogenesis of these diseases using an antigen-dependent approach. Circulating cutaneous lymphocyte associated antigen (CLA) positive (+) memory T cells are a subset of peripheral lymphocytes whose phenotype and function are related to immunological mechanisms in the skin. These cells are considered peripheral biomarkers of T-cell-mediated skin diseases. The co-culture of autologous epidermal cells with CLA+ T cells from psoriasis patients activated by Streptococcus pyogenes allows the reproduction of the ex vivo initial molecular events that occur during psoriatic lesion formation. With cooperation of autologous epidermal cells, S. pyogenes selectively activates CLA+ T cells both in guttate and plaque psoriasis, inducing key mediators, including an IL-17 response. Here we explore potential new mechanisms of psoriasis development including the influence of HLA-Cw6 on S. pyogenes CLA+ T cell activation in guttate psoriasis, the relevance of IL-9 on microbe induced IL-17 response in guttate and plaque psoriasis, and novel effector functions of Candida albicans. This review will summarize recent knowledge of psoriatic mechanisms elicited by microbes that have been studied through an innovative translational perspective based on CLA+ T cell mediated cutaneous immune response.